A Preliminary Study of Leadership and Innovation in Curriculum Change at Pre-University Programs in Malaysia - Wei How Delon Chai; Siew Huei Michelle Phua; Choo Wee Raymond Chiong (Acta Pedagogia Asiana, 2026)
In the rapidly evolving landscape of higher educa- tion, the integration of Education 4.0 principles necessitates a transformative approach to curriculum development. This paper investigates the pivotal roles of curriculum leaders in manag- ing curriculum changes within pre-university programs at two Malaysian higher education institutions. Employing a qualitative research methodology, this project involves in-depth interviews with key curriculum leaders, mainly the head of departments to explore their experiences and strategies in implementing innovative curriculum practices. The study aims to understand the differences in the roles that curriculum leaders play in leading and managing curriculum change and innovation specifically within pre-university level programs. The findings reveal that effective leadership is crucial in fostering a culture of innovation and continuous improvement. Curriculum leaders emphasised the importance of clear communication, comprehensive training, and a collaborative decision-making to address staff resistance and ensure successful implementation of changes to curriculum. Additionally, the study highlights the need for alignment between curriculum objectives and current educational trends, specifically in the context of digital marketing and critical thinking skills. This research underscores the significance of adaptive leadership in navigating the complexities of curriculum change, providing valuable insights for educational leaders and policymakers. Through embracing innovative practices and fostering a sup- portive environment for educators, institutions can enhance the relevance of effectiveness of their curricula, ultimately preparing students for the challenges of the modern workforce.